Effect of temperature on the growth of Myxococcus xanthus. - Janssen, G R (1977)
The cardinal growth characteristics of Myxococcus xanthus were examined from 14 to 40 degree C, and the examinations indicated that the organism is mesophilic in character. The maximum growth rate (0,3 doublings per h) was between 34 and 36 degree C and the temperature characteristic (micron) is 17,000 cal/mol (71,162 J/mol).